A bibliometric review of global research on the human-wildlife conflicts - Abas, Azlan; Rahman, Abdul Hafiz A.; Md Fauzi, Tengku Abdul Hadi T.; Yusof, Ahmad Hafizuddin M. (Frontiers in Environmental Science, 2025)
Human-wildlife conflict (HWC) affects both wildlife sustainability and human wellbeing. Current strategies for human-wildlife conflict are often fragmented and predominantly conservation-focused, lacking the necessary coordination and support from other impacted sectors. This study aims to explore the global research landscape on HWC through bibliometric analysis, using the Scopus database as the primary source and VOSviewer software for data analysis. A total of 4,822 articles were found in the study of human-wildlife conflict. This study has been researched by a total of 4,065 authors widely distributed all over the world, with most of the studies from the United States of America. This study also analyzed four type of clusters which are: a) Human-wildlife management, b) Human-animal physiology, c) Human-carnivore conflict, and d) Conservation and policy. The interest in HWC research has notably increased, with publications covering 24 subject categories in the Scopus Database. Most of these publications are found in Environmental Science, followed by Agricultural and Biological Sciences, and Social Sciences. This study highlights several gaps such as the lack of study in the social dimensions on HWC, lacking in the strategies towards human-wildlife co-existence, and policy gap between regional. This research contributes to community awareness and conservation initiatives, providing essential data and insights for policy-making towards the human-wildlife co-existence. This study emphasizes the involvement of various stakeholders—from local communities to governments and NGOs—assists in crafting comprehensive and inclusive policies.